Pembuatan Website Sekolah Sebagai Media Informasi dan Promosi - Rifqi Hammad; Andi Sofyan Anas; Pahrul Irfan; Ahmad Zuli Amrullah; Muhammad Zulfikri; Gilang Primajati; Rukmin Ulfa Ayu Lestari (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2022)
Website is an information technology that can be used to exchange information between users quickly by using the internet network. The website has been used by various institutions as a medium of information and promotion. One of them is school. Currently, SMKN 1 Jonggat does not have a website that is used as a medium of information and promotion. This causes problems for both the community and the school. People to get the information they need from schools, they have to come to school. The school also does not have a media that can be used to provide information and school promotion. Therefore, the service team held service activities that aimed to assist the school in creating a website that can be used as a medium of information and promotion. This activity is divided into three stages, namely planning, implementation and evaluation. The result of the planning stage is cooperation related to activities and data collection needed in making the website. At the implementation stage, the service team created a school website according to the results of the planning stage. The evaluation stage is the inspection stage related to the school website that has been created. The service team succeeded in creating a school website according to the needs of the school that can be used as a medium of information and promotion. With the school website, the problems of SMKN 1 Jonggat related to the distribution and delivery of information and promotions can be minimized